Organ-specific metastases obtained by culturing colorectal cancer cells on tissue-specific decellularized scaffolds. (June 2018) - Tian, Xi; Werner, Michael; Roche, Kyle; Hanson, Ariel; Foote, Henry; Yu, Stephanie; Warner, Samuel; Copp, Jonathan; Lara, Haydee; Wauthier, Eliane; Caster, Joseph; Herring, Laura; et al.
Abstract Metastatic disease remains the primary cause of mortality in cancer patients. Yet the number of available in vitro models to study metastasis is limited by challenges in the recapitulation of the metastatic microenvironment in vitro, and by difficulties in maintaining colonized-tissue specificity in the expansion and maintenance of metastatic cells. Here, we show that decellularized scaffolds that retain tissue-specific extracellular-matrix components and bound signalling molecules enable, when seeded with colorectal cancer cells, the spontaneous formation of three-dimensional cell colonies that histologically, molecularly and phenotypically resemble in vivo metastases. Lung and liver metastases obtained by culturing colorectal cancer cells on, respectively, lung and liver decellularized scaffolds retained their tissue-specific tropism when injected in mice. We also found that the engineered metastases contained signet ring cells, which has not previously been observed ex vivo. A culture system with tissue-specific decellularized scaffolds represents a simple and powerful approach for the study of organ-specific cancer metastases. A cell-culture method involving decellularized tissue scaffolds enables the spontaneous formation of cell colonies that phenotypically recapitulate in vivo organ-specific cancer metastases.